2016
DOI: 10.1007/s11743-016-1803-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Aryl Alkyl Sulfonates Based on Nonylphenol

Abstract: A series of nonylphenol-substituted alkyl sulfonates (C x NPAS, x = 8,10,12,14,16) with two hydrocarbon chains and two different hydrophilic groups has been synthesized from a-olefins and nonylphenol. The respective products have a ''pseudo-gemini'' surfactant structure. The structures of the C x NPAS have been characterized by IR, UV, 1 H nuclear magnetic resonance, electrospray ionization mass spectrometry, and elemental analysis. The effects of carbon chain length of the obtained surfactants on properties s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a similar context, Niu et al (2016) successfully reported the synthesis of a series of ARAS derived from nonylphenol. These compounds were synthesized from initial sulfonation of olefins followed by aromatic alkylation with nonylphenol and subsequent neutralization with sodium hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar context, Niu et al (2016) successfully reported the synthesis of a series of ARAS derived from nonylphenol. These compounds were synthesized from initial sulfonation of olefins followed by aromatic alkylation with nonylphenol and subsequent neutralization with sodium hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of a hydrophobic layer on the particle surface improves water repellency, reduces the capillary adhesion, modifies crystal growth, and reduces the tensile strength of the caking bond. Application of these coatings reduces the interfacial tension and improves the flowability of fertilizers [16]. Additionally, they contain basically a specific component that plays against the cake formation such as sulfonates, alkyl sulfates, amines, silicone, and petroleum-based components, etc.…”
Section: Introductionmentioning
confidence: 99%